Water - energy - food nexus narratives and resource securities: a global south perspective - Mabhaudhi, Tafadzwanashe; Senzanje, A.; Modi, A.; Jewitt, G.; Massawe, F. (Elsevier, 2022)
Water–Energy–Food Nexus Narratives and Resource Securities: A Global South Perspective provides a knowledge synthesis on the water–energy–food (WEF) nexus, focusing primarily on the global south. By presenting concepts, analytical tools, and case studies, the book serves as a practical resource for researchers, policymakers, and practitioners in sustainability and functional roles across all three sectors. It addresses key issues related to data availability, tools, indices, metrics, and application across multiple scales, beginning with a summary of existing knowledge. Finally, it examines the WEF nexus, presents global insights, and discusses future considerations and implications. This book presents an overview of existing knowledge on the WEF nexus and examines how such research aligns with emerging global WEF nexus perspectives, making it ideal for professionals, government entities, private industry, and the general public.